2020
DOI: 10.1038/s41438-020-0258-8
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of CRISPR/Cas-mediated cis-engineering in horticulture: unlocking the neglected potential for crop improvement

Abstract: Directed breeding of horticultural crops is essential for increasing yield, nutritional content, and consumer-valued characteristics such as shape and color of the produce. However, limited genetic diversity restricts the amount of crop improvement that can be achieved through conventional breeding approaches. Natural genetic changes in cisregulatory regions of genes play important roles in shaping phenotypic diversity by altering their expression. Utilization of CRISPR/Cas editing in crop species can accelera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 158 publications
(219 reference statements)
1
48
0
Order By: Relevance
“…Recently, the use of targeted genome editing using clustered regularly interspaced short palindromic repeats (CRISPR) and CRISPR-associated protein9 nuclease (Cas9) (CRISPR/Cas) has generated a lot of interest in various fields of plant biology including abiotic stress management [109]. CRISPR/Cas has been adopted in the field of plant developmental biology for characterizing genes as well as to underpin the molecular mechanisms behind various plant traits [110]. It has been used in the model plants such as Arabidopsis and tobacco earlier and likewise, now it is being utilized effectively for crop plants like sorghum, rice, wheat, maize, soybean as well as woody plants.…”
Section: Strategies To Combat Abiotic Stresses In Plantsmentioning
confidence: 99%
“…Recently, the use of targeted genome editing using clustered regularly interspaced short palindromic repeats (CRISPR) and CRISPR-associated protein9 nuclease (Cas9) (CRISPR/Cas) has generated a lot of interest in various fields of plant biology including abiotic stress management [109]. CRISPR/Cas has been adopted in the field of plant developmental biology for characterizing genes as well as to underpin the molecular mechanisms behind various plant traits [110]. It has been used in the model plants such as Arabidopsis and tobacco earlier and likewise, now it is being utilized effectively for crop plants like sorghum, rice, wheat, maize, soybean as well as woody plants.…”
Section: Strategies To Combat Abiotic Stresses In Plantsmentioning
confidence: 99%
“…However, like most plant species, almost no knowledge has been generated regarding the structure of promoters and other regulatory sequences in tomato, and no prior information is currently available for CREs and their interactions in the promoter of SlGABA-T1. Even though prior knowledge would facilitate and speed the process, cis-engineering could be implemented if a multiplexed CRISPR/Cas9 system was developed (Li et al, 2020). For this, we assembled a vector containing four gRNAs that was designed within a region 2 kbp upstream of the SlGABA-T1 start codon and transformed in Micro-Tom (Figure 2A).…”
Section: Alternative Prospects For Gaba Improvement Using Nbptsmentioning
confidence: 99%
“…Many examples have reported that mutations in cis -regulatory elements (CREs) produce significant phenotypic and morphological changes that have been selected during domestication ( Meyer and Purugganan, 2013 ; Swinnen et al., 2016 ). In tomato, changes in CREs and promoter regions were translated in elongated ( SlSUN ) and larger fruits ( FW2.2 , FW3.2 , SlWUS ) or those with improved β-carotene contents ( Slcys-B ) ( van der Knaap et al., 2014 ; Li et al., 2020 ) as just a few relevant examples. However, despite the great potential of this approach, currently, the vast majority of CRISPR/Cas9 studies focus on targeting coding sequences for null allele editing or controlling transcription by activation (CRISPRa) or inhibition (CRISPRi), and only 15 studies so far have reported successful applications of cis -engineering ( Li et al., 2020 ).…”
Section: Alternative Prospects For Gaba Improvement Using Nbptsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rapid nucleic acid detection is an important part of many applications in human health and biotechnology, including the identifying of infectious diseases, agricultural pathogens, or circulating DNA or RNA associated with disease. [17][18][19] Standard methods to amplify nucleic acids for detection (such as PCR) are effective but require instrumentation that is not portable, precluding their deployment in the field [20,21]. CRISPR-Cas-based approaches are being tested to treat hereditary, infectious, and many other diseases.…”
Section: Detection Of Nucleic Acids By Crispr-casmentioning
confidence: 99%